Phase equilibria measurements and modelling of {water + cyclohexane + ethanol + 1-propanol} system - Erasmus, Amanda Stephanie (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.